An open-access plug-in program for 3D modelling distinct material properties of cortical and trabecular bone - Gregory R. Roytman; Matan Cutler; Kenneth Milligan; Steven M. Tommasini; Daniel H. Wiznia (BMC Biomedical Engineering, 2022)
Abstract Background Finite element modelling the material behavior of bone in-silico is a powerful tool to predict the best suited surgical treatment for individual patients. Results We demonstrate the development and use of a pre-processing plug-in program with a 3D modelling image processing software suite (Synopsys Simpleware, ScanIP) to assist with identifying, isolating, and defining cortical and trabecular bone material properties from patient specific computed tomography scans. The workflow starts by calibrating grayscale values of each constituent element with a phantom – a standardized object with defined densities. Using an established power law equation, we convert the apparent density value per voxel to a Young’s Modulus. The resulting “calibrated” scan can be used for modeling and in-silico experimentation with Finite Element Analysis. Conclusions This process allows for the creation of realistic and personalized simulations to inform a surgeon’s decision-making. We have made this plug-in program open and accessible as a supplemental file.